Komunikasi Matematis Siswa SMP dalam Menyelesaikan Masalah Teorema Pythagoras Ditinjau dari Gender - Florensia, Tasya; Juniati, Dwi; Khabibah, Siti (Universitas Dr. Soetomo, 2025)
Abstract Written mathematical communication is important in learning mathematics because it helps students convey ideas systematically and revise solutions more easily. In problem solving, mathematical communication serves to understand, design, and communicate strategies in writing. One of the factors that influences mathematical communication is gender, which shapes students' thinking, communication patterns, and problem-solving strategies. This study aims to describe junior high school students' mathematical communication in solving Pythagorean Theorem problems in terms of gender. This study used a qualitative descriptive design, involving two students who were purposively selected and identified through the Bem Sex Role Inventory as students with dominant feminine or masculine characteristics. The results show that both students demonstrated mathematical communication in understanding the problem, planning the solution, and implementing the solution. (1) The male student illustrated and wrote down accurate but incomplete information. He planned the solution by illustrating and writing down the steps and formulas accurately and fluently but incompletely. Illustrations, calculation processes, and conclusions were expressed accurately and fluently, but were incomplete. (2) The female student wrote down information and a solution plan accurately and fluently, but they were incomplete. She expressed the calculation process accurately and fluently, but it was incomplete; while the conclusion was accurate, complete, and fluent. Keywords: gender; student mathematical communication; problems; pythagorean theorem Abstrak Komunikasi matematis tulisan penting dalam pembelajaran matematika karena membantu siswa menyampaikan ide secara sistematis dan merevisi solusi dengan lebih mudah. Dalam penyelesaian masalah, komunikasi matematis berfungsi untuk memahami, merancang, dan mengkomunikasikan strategi secara tertulis. Salah satu faktor yang mempengaruhi komunikasi matematis adalah gender, yang turut membentuk cara berpikir, pola komunikasi, dan strategi penyelesaian masalah siswa. Penelitian ini bertujuan untuk mendeskripsikan komunikasi matematis siswa SMP dalam menyelesaikan masalah Teorema Pythagoras ditinjau dari gender. Penelitian ini menggunakan desain deskriptif kualitatif, dengan melibatkan dua siswa yang dipilih secara purposif dan diidentifikasi melalui Bem Sex Role Inventory sebagai siswa dengan ciri feminin atau maskulin dominan. Hasil menunjukkan bahwa kedua siswa menampilkan komunikasi matematis pada langkah memahami masalah, merencanakan penyelesaian, dan melaksanakan penyelesaian. (1) Siswa laki-laki mengilustrasikan dan menuliskan informasi akurat namun kurang lengkap. Merencanakan penyelesaian dengan mengilustrasikan dan menuliskan langkah-langkah dan rumus dengan akurat dan lancar namun kurang lengkap. Ilustrasi, proses perhitungan, dan kesimpulan diungkapkan dengan akurat dan lancar, namun kurang lengkap. (2) Siswa perempuan menuliskan informasi dan rencana penyelesaian akurat dan lancar, namun kurang lengkap. Mengungkapkan proses perhitungan dengan akurat dan lancar, namun kurang lengkap, sedangkan kesimpulan sudah akurat, lengkap, dan lancar. Kata Kunci: gender; komunikasi matematis siswa; masalah; teorema pythagoras